Luminescence and Judd-Ofelt analysis of Nd3+ ion doped oxyfluoride boro-tellurite glass for near-infrared laser application. (2021) - Yuliantini, L.; Djamal, M.; Hidayat, R.; Boonin, K.; Kaewkhao, J.; Yasaka, P.
Abstract: Nd 3+ ion-doped oxyfluoride boro-tellurite glass has been successfully developed by melt and quenching technique. The composition of present glass was (30-x)TeO2 -30B2 O3 -10ZnF2 -30BaO-xNd2 O3 where x = 0.00, 0.05, 0.10, 0.50, 1.00, and 1.50 mol%. The quenching concentration is found in the 0.5 mol% Nd2 O3 in the glass system. The density, molar volume and refractive index of quenching concentration is respectively 3.80 g/cm 3, 33.15 cm 3 /mol, and 1.631. The intensity of absorption spectra shows the enhancement with increasing Nd 3+ ion concentration in the glass system. The highest intensity of absorption spectra come from 4 I9/2 → 4 G5/2 + 2 G7/2 transition centred at 584 nm. Meanwhile, the highest intensity of excitation spectra with λem =1072 nm occurs due to 4 I9/2 → 4 G5/2 + 2 G7/2 transition centred at 575 nm. The emission spectra show several transitions originated from the metastable level of 4 F3/2 to 4 I9/2 (919 nm), 4 I11/2 (1072 nm), and 4 I13/2 (1340 nm) under λex =575 nm. The strongest emission peak of present glass is centred at 1072 nm ( 4 F3/2 → 4 I11/2 ). The 4 F3/2 → 4 I11/2 transition lifetime is 138.36 µs. The present glass possesses longer lifetime than other reported Nd 3+ :glasses. The results show that Nd 3+ ion-doped oxyfluoride boro-tellurite glass is a potential material for optical devices application such as near-infrared laser gain medium, optical telecommunication, and imaging